2018
DOI: 10.1039/c8ra05047c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different pretreatments on the synergistic effect of cellulase and xylanase during the enzymatic hydrolysis of sugarcane bagasse

Abstract: The synergistic effects between cellulase and xylanase were substrate and time specific during the hydrolysis of pretreated SCB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…The fiber purification process consisted of an alkali treatment that solubilized the lignin, pectins, hemicelluloses, proteins, and low-molecular weight sugars followed by a bleaching process that removed the lignin residues . The removal of part of the hemicellulose and lignin fractions is required in order to facilitate the enzymatic hydrolysis reactions, since these components constitute a natural cell wall barrier to the cellulose fibers. , A linear relationship between lignin removal and cellulose digestibility by enzymatic action has been demonstrated previously. ,, …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The fiber purification process consisted of an alkali treatment that solubilized the lignin, pectins, hemicelluloses, proteins, and low-molecular weight sugars followed by a bleaching process that removed the lignin residues . The removal of part of the hemicellulose and lignin fractions is required in order to facilitate the enzymatic hydrolysis reactions, since these components constitute a natural cell wall barrier to the cellulose fibers. , A linear relationship between lignin removal and cellulose digestibility by enzymatic action has been demonstrated previously. ,, …”
Section: Resultsmentioning
confidence: 95%
“…The purification procedure was necessary to ensure an efficient removal of noncellulosic materials, especially lignin, which hinder the access of enzymes to the cellulose, impairing the viability of enzymatic hydrolysis. 24 The methodology used followed a procedure adapted from Flauzino Neto et al 25 Briefly, 5 g of fibers were treated in 1 L of a 10% (w/w) sodium hydroxide aqueous solution for 1 h at 80 °C, under mechanical stirring, washed with distilled water until neutral pH, and then dried at 50 °C for 24 h. After this alkali treatment, the fibers were bleached with a solution made up of equal parts (v/v) of acetate buffer (27 wt % NaOH and 7.5% (v/v) glacial acetic acid, in distilled water) and aqueous sodium chlorite (1.7 wt % NaClO 2 in water). The proportion used in this bleaching treatment was 1 g of fiber per 50 mL of solution.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…was observed during the initial hydrolysis stage but it decreased in the later hydrolysis stage (Huang et al, 2018). In addition, it was observed that the digestibility of cellulase was increased with the digestibility of xylan in the hydrolysis of pretreated sugarcane bagasse substrates (Huang et al, 2018). Similarly, supplementing commercial cellulase (Sigma-Aldrich, USA) with BGL was compared for the hydrolysis of microcrystalline cellulase, native corn straw and steam pretreated corn straw and the results showed an increase in glucose release by 62, 94, and 95%, respectively (Zhang et al, 2017).…”
Section: Synergistic Enzyme Cooperationmentioning
confidence: 88%
“…was observed during the initial hydrolysis stage but it decreased in the later hydrolysis stage (Huang et al, 2018). In addition, it was observed that the digestibility of cellulase was increased with the digestibility of xylan in the hydrolysis of pretreated sugarcane bagasse substrates (Huang et al, 2018).…”
Section: Synergistic Enzyme Cooperationmentioning
confidence: 98%
“…Similarly, the xylanase family 10 Xyn10Z responsible for xylan solubilization was frequently chosen for artificial cellulosomes [6,22]. The cellulase-xylanase synergy that facilitates the decomposition of complex substrates was noticed in previous studies [16,[25][26][27][28][29]. In addition, the saccharolytic enzymes originated from the aerobic thermophilic bacterium Thermobifida fusca, with thermostability and potent catalytic efficiency [30], are identified as important starting materials for constructing DCs in several studies [16,29,[31][32][33].…”
Section: Integration Of Laccase Into Designer Cellulosomesmentioning
confidence: 99%